Development of an enzymatic fiber-optic biosensor for detection of halogenated hydrocarbons - Bidmanova, Sarka; Chaloupkova, Radka; Damborsky, Jiri; Prokop, Zbynek (Analytical and bioanalytical chemistry, 2010)
An enzyme-based biosensor was developed by co-immobilization of purified enzyme haloalkane dehalogenase (EC 3.8.1.5) and a fluorescence pH indicator on the tip of an optical fiber. Haloalkane dehalogenase catalyzes hydrolytic dehalogenation of halogenated aliphatic hydrocarbons, which is accompanied by a pH change influencing the fluorescence of the indicator. The pH sensitivity of several fluorescent dyes was evaluated. The selected indicator 5(6)-carboxyfluorescein was conjugated with bovine serum albumin and its reaction was tested under different immobilization conditions. The biosensor was prepared by cross-linking of the conjugate in tandem with haloalkane dehalogenase using glutaraldehyde vapor. The biosensor, stored for 24 h in 50 mM phosphate buffer (pH 7.5) prior to measurement, was used after 15 min of equilibration, the halogenated compound was added, and the response was monitored for 30 min. Calibration of the biosensor with 1,2-dibromoethane and 3-chloro-2-(chloromethyl)-1-propene showed an excellent linear dependence, with detection limits of 0.133 and 0.014 mM, respectively. This biosensor provides a new tool for continuous in situ monitoring of halogenated environmental pollutants.
Keywords: skot; fluorescenční barviva; molekulární struktura; Cattle; Hydrocarbons, Halogenated; Molecular Structure; biosenzitivní techniky; technologie optických vláken; Biosensing Techniques; Fiber Optic Technology; halogenované uhlovodíky; Fluorescent Dyes; Animals; enzymy imobilizované; Enzymes, Immobilized; zvířata